(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper tries to bring a systematic unity of the legal institutes ruling the therapeutic treatment for mental illness. With reference to the structure of public health services, the extension of contractual liability as prescribed by art. 1218 (Italian civil code), might allow to avoid that the lack of a positive law could lead to a lack of rights. The fact that the therapeutic treatment can be imposed to the patient just to ensure public safety is not in compliance with article 32 (of the Italian Constitution) and with the principle of solidarity. The case of the “tutor and administrator of incapable” deciding whether agreeing on the treatment or not must be subsumed under article 32 paragraph 2 of the Italian Constitution, Public administration’s “weak identity” in the psychiatric environment affects the health professionals’ liabilities.